Comprehensive Case Report: Bipolar Affective Disorder with a Current Manic Episode and Psychotic Symptoms in an Adolescent Male Triggered by Chronic Bullying in a Rural Area of Southwest Sumba - Sri Maharani, Ni Putu Intan; Wisuda Manik, I Gusti Ngurah (Jurnal Indonesia Sosial Sains, 2026)
Bipolar affective disorder (BAD) in adolescents is a chronic psychiatric condition with complex clinical manifestations and high risk of psychotic symptoms. Environmental factors, particularly bullying, have been identified as major stressors that can trigger disease onset through the kindling phenomenon. In remote areas such as Southwest Sumba, diagnostic challenges and limited treatment access are major obstacles to patient recovery. To report the clinical journey and successful management of an adolescent male with BAD manic episode with psychotic symptoms triggered by chronic bullying in a rural setting. Case report with data collection through in-depth family interviews, clinical mental status observation, and medical record review over a six-month period. Findings: Patient MPB (17 years) experienced systematic physical and verbal bullying during junior high school leading to school dropout. Psychotic symptoms manifested as visual hallucinations of a "woman in white" giving commands to self-harm. Diagnosis F31.2 (BAD manic episode with psychotic symptoms) was established based on PPDGJ-III. Combination therapy with risperidone (2x2 mg) and divalproex sodium (2x250 mg) showed effective synergy in stabilizing dopaminergic and GABAergic neurotransmission. Within six months, the patient showed stable symptom remission, returned to vocational school (SMK), and achieved GAF score improvement from 70-61 to 90-81. Key recommendations include strengthening anti-bullying policies in schools and expanding access to community-based mental health services in remote (3T) areas.